The nature, extent and impact of the brain drain in Zimbabwe and South Africa - Gwaradzimba, Ellen; Shumba, Almon (Acta Academica: Critical views on society, culture and politics, 2010)
Brain drain is regarded as one of the greatest threats to socio-economic development in Africa. The need to reverse brain drain and reposition Africa in the twenty-first century cannot be overemphasised. The current situation in African countries demands that Africa should embark on a radical project to redeem itself from poverty, underdevelopment, disease, and hunger. This article examines the nature, extent and impact of the brain drain in Zimbabwe and South Africa. The problem of brain drain is urgent and merits high-level attention by African governments